Globalization of Mobile and Wireless Communications Today and in 2020 - Prasad, Ramjee; Dixit, Sudhir; Nee, Richard van; Ojanpera, Tero (Springer eBooks., 2011)
Globalization of Mobile and Wireless Communications is a collection of cutting-edge research in mobile and wireless communications with impact on developments as far forward as 2020 and beyond. The book draws upon the insights and performed research work of leading experts in the field. Topics of discussion are related but not limited to spectrum-efficient radio interface technologies, enabling technologies for reconfigurability, wireless sensor networks, cognitive networks, coherent wireless transmission, algorithmic design, middleware for novel services and applications. The material has been edited to provide a vision for the future of mobile and wireless, towards a dynamic communication system that breaks down the barriers between communications means; and evolves and integrates business models and culture to match the technological evolution. In addition, strategies on how to overcome the technological challenges for achieving that vision are also outlined.